Study of the Evolution of Environmental Management in Industrial Enterprises - Ormazabal, Marta; Sarriegi, Jose María (M+A. Revista Electrónica de Medioambiente, 2012)
Environmental Management has recently become an essential issue for companies. Nevertheless, not all the companies have reached the same maturity level. Through some workshops with environmental experts, information on those aspects that affect environmental management has been collected to demonstrate that the evolution of environmental management is similar in every company. Some factors, policies, indicators and behaviors that affect environmental management over time have been defined. This study allows companies to identify in which maturity state they are in and what are the steps that they have to follow to go towards environmental excellence.